2015
DOI: 10.1001/jamapediatrics.2015.0310
|View full text |Cite
|
Sign up to set email alerts
|

Practice- and Community-Based Interventions to Increase Human Papillomavirus Vaccine Coverage

Abstract: IMPORTANCE-Vaccines against human papillomavirus (HPV) are recommended for routine use in adolescents aged 11 to 12 years in the United States, but uptake remains suboptimal. Educational interventions focused on parents and patients to increase coverage have not generally demonstrated effectiveness. OBJECTIVE-To systematically review the literature on effectiveness of interventions conducted at the practice or community level to increase uptake of HPV vaccines in the United States. EVIDENCE REVIEW-Keyword sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
154
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(154 citation statements)
references
References 37 publications
(155 reference statements)
0
154
0
Order By: Relevance
“…Electronic health record (EHR) systems can automate reminder-recalls for patients due for HPV vaccination, generate reminder prompts for providers to administer the vaccine, and help facilitate nurse-only immunization visits and walk-in immunization hours that can make completion of the HPV vaccine series easier. Strategies such as reminder-recalls for patients and reminder prompts for providers have often, but not always, been successful at increasing rates of vaccination, 7,8 but implementation of these strategies is inconsistent. In addition, EHRs can generate reports to track the effect of strategies to increase HPV vaccination and potential procedural challenges during implementation (eg, vaccine supply, parents refusing or delaying vaccination, etc).…”
Section: System-level Approachesmentioning
confidence: 99%
“…Electronic health record (EHR) systems can automate reminder-recalls for patients due for HPV vaccination, generate reminder prompts for providers to administer the vaccine, and help facilitate nurse-only immunization visits and walk-in immunization hours that can make completion of the HPV vaccine series easier. Strategies such as reminder-recalls for patients and reminder prompts for providers have often, but not always, been successful at increasing rates of vaccination, 7,8 but implementation of these strategies is inconsistent. In addition, EHRs can generate reports to track the effect of strategies to increase HPV vaccination and potential procedural challenges during implementation (eg, vaccine supply, parents refusing or delaying vaccination, etc).…”
Section: System-level Approachesmentioning
confidence: 99%
“…2 Clinically and statistically significant improvements in HPV series initiation, completion, meningococcal and Tdap vaccinations were observed in primary care practices implementing the 4 Pillars™ Practice Transformation Program. Increases in vaccine uptake resulted in post intervention rates that were higher than both state and national average coverage levels.…”
Section: Discussionmentioning
confidence: 95%
“…A review of interventions to increase HPV vaccinations suggested that health care settings are a desirable environment for successful vaccination interventions. 2 This conclusion is strengthened by the preponderance of evidence that links physician recommendation to uptake of HPV vaccine. 3,4 …”
Section: Introductionmentioning
confidence: 99%
“…One systematic review found that reminder systems for vaccination and feedback to physicians were two common methods for improving HPV vaccination rates. 13 …”
Section: Introductionmentioning
confidence: 99%